Strategi Adaptasi Mahasiswa Papua terhadap Budaya Banyumas (Studi Deskriptif pada Mahasiswa Papua di Universitas Jenderal Soedirman Purwokerto) - Aprilia Yunita; Sulyana Dadan; Tri Rini Widyastuti (Universitas Lambung Mangkurat, 2024)
Papuan students face tough challenges when they are in a new place because they are physically different from the majority of Indonesian society. Apart from that, they have to face various challenges such as (1) language differences; (2) differences in community characteristics; and (3) the existence of negative stereotypes. This research aims to find out the strategies used by Papuan students to be able to adapt to Banyumas culture in Purwokerto City. The research method uses qualitative methods with a descriptive approach. The technique for determining informants used purposive sampling with the research target being Papuan students who received ADik scholarships in Unsoed and had lived in Purwokerto for at least one year. The data form of interviews and observations were analyzed using interactive analysis techniques from Miles and Huberman using the symbolic interactionism theory from Herbert Blumer and George H. Mead. Test the validity of the data using source triangulation. The research results show that Papuan students have several strategies to adapt to Banyumas culture in Purwokerto City, namely trying to mingle with other students and the local community; joining various organizations in order to expand relationships and as a platform to develop talent; learning to understand ngapak language as an effort to make Papuan students feel more accepted in the Purwokerto; and understand the characteristics of the Banyumas community.